Tantalum oxide optical coating material and preparation method thereof

By adopting tantalum oxide optical coating materials with high α-Ta2O5 phase purity and their preparation methods, the existing tantalum pentoxide coating materials have been solved, and the coating materials with high transmittance and high density have been achieved, and the working efficiency of the coating is improved.

CN120117897APending Publication Date: 2025-06-10LEADING THIN FILM MATERIALS (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510231138.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The existing tantalum pentoxide coating materials have low transmittance and are prone to problems such as gas phase instability during the pre-fusion process, resulting in a decrease in working efficiency.

Method used

The tantalum oxide optical coating material with high α-Ta2O5 phase purity and its preparation method are used to improve the transmittance and density of the coating material through specific process steps and process parameters (such as sintering temperature, insulation time, heating rate, etc.).

Benefits of technology

The transmittance and density of the coating material is significantly improved, the air pressure stability in the pre-fusion stage is improved, and the working efficiency of the coating is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120117897A_ABST
    Figure CN120117897A_ABST
Patent Text Reader

Abstract

The invention provides a tantalum oxide optical coating material, the tantalum oxide optical coating material is black oxygen-lost tantalum pentoxide, the main phase is alpha-Ta2O5, and the phase purity of alpha-Ta2O5 is greater than or equal to 96%. The high-tantalum-oxide optical coating material is high in phase purity, the transmittance of a coated film layer is high, and the problems that the air pressure is unstable and the coating efficiency is reduced due to low phase purity in the coating pre-melting stage can be greatly solved; the invention also provides a preparation method of the tantalum oxide optical coating material, which comprises the following steps: granulating, crushing and sieving tantalum pentoxide powder with a certain particle size to obtain a granulated material; carrying out first compression molding on the granulation material to obtain a first molding material; the first forming material is crushed into particles and sieved, and particles with the particle size being 1-5 mm are obtained; performing primary sintering on the particles to obtain a first sintered material; performing vacuum sintering on the first sintered material to obtain a second sintered material; and screening the second sintered material, and assembling the second sintered material into a particle aggregate to obtain the tantalum pentoxide optical coating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optical coating materials, and particularly relates to tantalum oxide optical coating materials and a preparation method thereof. Background Art

[0002] In the field of optical thin films, tantalum pentoxide is an important high refractive index material, and its light transmission region is about 0.3 - 10 μm, covering a wide range from near ultraviolet, visible light to infrared bands. Usually, tantalum pentoxide is combined with low refractive index silica materials to prepare various optical thin films such as filter films, high reflection films, and antireflection films. In recent years, with the rapid development of electronic technology, tantalum pentoxide thin films have been gradually applied to various electronic components such as gas sensors, impedance elements, and memory electrochromic devices due to their excellent chemical stability, relatively high dielectric constant, and high breakdown voltage, and their properties have once again attracted people's attention.

[0003] In the prior art, the conventional preparation method of tantalum pentoxide is vacuum sintering method. However, the transmittance of the film layer after coating with the tantalum pentoxide coating material prepared by the existing preparation method needs to be improved, and there are often problems such as unstable gas phase during the pre-melting process, which further prolongs the gas pressure stabilization time during the pre-melting process and reduces the working efficiency. Summary of the Invention

[0004] In view of the above technical problems, the present application provides tantalum oxide optical coating materials and a preparation method thereof.

[0005] To achieve the above object, the present application proposes the following technical solutions: In the first aspect, a tantalum oxide optical coating material is provided. The tantalum oxide optical coating material is black oxygen-deficient tantalum pentoxide, and the main phase is α-Ta 2 O 5 , where the phase purity of α-Ta 2 O 5 is ≥ 96%.

[0006] Further, the atomic ratio of tantalum to oxygen in the tantalum oxide optical coating material is 2:(4.6 - 4.98).

[0007] Further, the loose bulk density of the tantalum oxide optical coating material is 4.0 - 4.3 g / cm 3 .

[0008] Further, the relative density of the tantalum oxide optical coating material is above 80%.

[0009] In the second aspect, a preparation method of tantalum oxide optical coating material is provided, including: Tantalum pentoxide powder with a particle size D50 of 0.3 - 2.8 μm is granulated, crushed, and sieved through a 80-mesh sieve to obtain granulated material; The granulated material is subjected to first pressing and forming to obtain a first formed material; The first formed material is crushed into particles and sieved to obtain particulate matter with a particle size of 1 - 5 mm; The particulate matter with a particle size of 1 - 5 mm is subjected to primary sintering to obtain a first sintered material; The first sintered material is subjected to vacuum sintering to obtain a second sintered material; The second sintered material is screened and assembled into a particle aggregate to obtain a tantalum pentoxide optical coating material.

[0010] Further, after the first formed material is crushed into particles and sieved, the particulate matter with a particle size less than 1 mm is ground and subjected to second pressing and forming to obtain a second formed material. The second formed material is crushed and sieved to obtain particulate matter with a particle size of 1 - 5 mm, and the particulate matter with a particle size greater than 5 mm is crushed and sieved again to obtain particulate matter with a particle size of 1 - 5 mm.

[0011] Further, the sintering temperature of the primary sintering is 1000 - 1500 °C; the heat preservation duration of the primary sintering is 1 - 6 h.

[0012] Further, the heating rate of the primary sintering is not higher than 10 °C / min.

[0013] Further, the cooling after the primary sintering is as follows: cooling at a cooling rate not higher than 5 °C / min to below 800 °C and then cooling with the furnace.

[0014] Further, the temperature of the vacuum sintering is 1500 - 1800 °C, and the heat preservation duration of the vacuum sintering is 1 - 10 h.

[0015] Further, the vacuum degree of the vacuum sintering is 1.0×10 -3 ~4.0×10 -3 MPa.

[0016] Further, the heating rate of the vacuum sintering is not higher than 10 °C / min.

[0017] Further, the cooling after the vacuum sintering is as follows: cooling at a cooling rate not higher than 5 °C / min to below 1400 °C and then cooling with the furnace.

[0018] Further, the granulation includes: mixing and blending tantalum pentoxide powder with an appropriate amount of water, standing, and then sieving to obtain a blended material, and subjecting the blended material to pressing granulation.

[0019] Further, the mass ratio of the tantalum pentoxide powder to water is 6 - 9:4 - 1.

[0020] Further, the mixing is carried out by a mixer; the mixing time is 2 to 10 h; the standing time is 20 to 30 h.

[0021] Further, the pressure for pressing and granulating is 15 to 40 MPa.

[0022] Further, the forming densities of the first pressing and forming and the second pressing and forming are independently 3.2 to 4.0 g / cm 3 .

[0023] Further, the second sintered material is sieved and assembled into a particle aggregate, including: the second sintered material is sieved to obtain particles with a particle size of 0.5 to 3 mm, and then the obtained particles are assembled into a particle aggregate with a loose density of 4.0 to 4.3 g / cm 3 .

[0024] Further, the purity requirement of the tantalum pentoxide powder is ≥99.95%.

[0025] Further, the particle size D50 of the tantalum pentoxide powder is 0.3 to 2.5 μm, preferably 0.3 to 2 μm.

[0026] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: Provide a tantalum oxide optical coating material, which is black oxygen-deficient tantalum pentoxide, and the main phase is α-Ta 2 O 5 , where the phase purity of α-Ta 2 O 5 is ≥96%. The α-Ta 2 O 5 of the high tantalum oxide optical coating material has a high phase purity, and the transmittance of the deposited film layer is high, which can greatly improve the problems of unstable air pressure and reduced coating efficiency caused by low phase purity in the pre-melting stage of coating.

[0027] The preparation method of the provided tantalum oxide optical coating material is simple, easy to operate, low in cost and energy consumption, convenient for mass production, and can prepare a tantalum oxide optical coating material with a high α-Ta 2 O 5 phase purity. The transmittance of the deposited film layer is high, and the prepared tantalum oxide optical coating material with a high α-Ta 2 O 5 phase purity can greatly improve the problems of unstable air pressure and reduced coating efficiency caused by low phase purity in the pre-melting stage of coating. Description of the Drawings

[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0029] Figure 1 XRD analysis pattern of the tantalum pentoxide coating material prepared in Example 2.

[0030] Figure 2 Analysis pattern of the phase purity and film layer transmittance of the tantalum pentoxide coating materials prepared in Example 1 and Comparative Examples 1 - 3.

[0031] Figure 3 SEM image of the high - transmittance tantalum pentoxide coating material prepared in Example 6. Detailed implementation manners

[0032] The applicant has found through research that the tantalum pentoxide optical coating materials prepared by the existing sintering methods often have problems such as low phase purity, such as co - existence of two phases, co - existence of three phases, etc. The reduction of the α - Ta 2 O 5 phase purity will greatly reduce the transmittance of the film layer after coating; and the lower phase purity will cause problems such as unstable gas phase during the pre - melting process due to the existence of different phases, thereby prolonging the time for the gas pressure to stabilize during the pre - melting process and reducing the working efficiency. Based on this, a tantalum oxide optical coating material with high α - Ta 2 O 5 phase purity and its preparation method have been developed.

[0033] The present application provides a tantalum oxide optical coating material, which is black oxygen - deficient tantalum pentoxide, and the main phase is the high - temperature phase α - Ta 2 O 5 , where the phase purity of α - Ta 2 O 5 ≥96% (that is, the percentage of the α - Ta 2 O 5 phase in the total crystal system quantity exceeds 96%), such as 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%, 100%, etc. The inventor has found through research that the increase in the phase purity of the high - temperature phase α - Ta 2 O 5 in the tantalum oxide optical coating material is beneficial to significantly improve the transmittance of the coating. The black oxygen - deficient tantalum pentoxide coating material with high phase purity (phase purity of α - Ta 2 O 5 ≥96%) has the advantage of high transmittance when coating.

[0034] In some preferred embodiments, the atomic ratio of tantalum to oxygen in the tantalum oxide optical coating material is 2:(4.6 - 4.98), such as 2:4.6, 2:4.61, 2:4.62, 2:4.63, 2:4.64, 2:4.65, 2:4.66, 2:4.67, 2:4.68, 2:4.69, 2:4.7, 2:4.71, 2:4.72, 2:4.73, 2:4.74, 2:4.75, 2:4.76, 2:4.77, 2:4.78, 2:4.79, 2:4.8, 2:4.81, 2:4.82, 2:4.83, 2:4.84, 2:4.85, 2:4.86, 2:4.87, 2:4.88, 2:4.89, 2:4.9, 2:4.91, 2:4.92, 2:4.93, 2:4.94, 2:4.95, 2:4.96, 2:4.97, 2:4.98, etc.

[0035] In some preferred embodiments, the loose bulk density of the tantalum oxide optical coating material is 4.0 - 4.3 g / cm 3 , such as 4.0 g / cm 3 , 4.1 g / cm 3 , 4.2 g / cm 3 , 4.3 g / cm 3 , etc. By controlling the loose bulk density, the weight of the product per unit volume can be controlled, ensuring that the particle weight is consistent each time it is used and guaranteeing the stability of the subsequent use.

[0036] In some preferred embodiments, the relative density of the tantalum oxide optical coating material is above 80%, such as 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 99%, etc. The increase in the relative density of the coating material is beneficial to improving the quality of the coating film and the performance of the film layer.

[0037] The present application provides a method for preparing a tantalum oxide optical coating material, including: Tantalum pentoxide powder with a particle size D50 of 0.3 - 2.8 μm is granulated, crushed, and sieved through a 80 - mesh sieve to obtain granulated material; The granulated material is subjected to first pressing and forming to obtain a first formed material; The first formed material is crushed into particles and then sieved to obtain particles with a particle size of 1 - 5 mm; The particles with a particle size of 1 - 5 mm are subjected to primary sintering to obtain a first sintered material; The first sintered material is subjected to vacuum sintering to obtain a second sintered material; The second sintered material is screened and assembled into a particle aggregate to obtain the tantalum oxide optical coating material.

[0038] In order to improve the utilization rate of the first formed material, the particulate matter that does not meet the particle size conditions after sieving is further processed. In some preferred embodiments, after the first formed material is crushed into particles and sieved, the particulate matter with a particle size less than 1 mm is ground and then secondarily compression-molded to obtain a second formed material. The second formed material is crushed and sieved to obtain particulate matter with a particle size of 1 - 5 mm, and the particulate matter with a particle size greater than 5 mm is crushed and sieved again to obtain particulate matter with a particle size of 1 - 5 mm.

[0039] In some preferred embodiments, the sintering temperature of the first sintering is 1000 - 1500 °C, such as 1000 °C, 1050 °C, 1100 °C, 1150 °C, 1200 °C, 1250 °C, 1300 °C, 1350 °C, 1400 °C, 1450 °C, 1500 °C, etc.; the heat preservation duration of the first sintering is 1 - 6 h, such as 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, etc.

[0040] In some preferred embodiments, the heating rate of the first sintering is not higher than 10 °C / min, such as 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min, 10 °C / min, etc.

[0041] In some preferred embodiments, the cooling after the first sintering is as follows: cooling at a cooling rate not higher than 5 °C / min (such as 5 °C / min, 4 °C / min, 3 °C / min, 2 °C / min, 1 °C / min, etc.) to below 800 °C (such as 800 °C, 750 °C, 700 °C, 650 °C, 600 °C, 550 °C, 500 °C, 450 °C, 400 °C, 350 °C, 300 °C, 250 °C, 200 °C, 150 °C, 100 °C, 50 °C, room temperature, etc.) and then cooling with the furnace.

[0042] In some embodiments, during the first sintering, the particulate matter with a particle size above 1 mm and less than 5 mm (such as 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm, 2.2 mm, 2.5 mm, 2.8 mm, 3 mm, 3.2 mm, 3.5 mm, 3.8 mm, 4 mm, 4.2 mm, 4.5 mm, 4.8 mm, etc.) is placed in an alumina crucible, and then the crucible is placed in a sintering furnace for the first sintering.

[0043] In some preferred embodiments, the temperature of the vacuum sintering is 1500 - 1800 °C, such as 1500 °C, 1550 °C, 1600 °C, 1650 °C, 1700 °C, 1750 °C, 1800 °C, etc., and the heat preservation duration of the vacuum sintering is 1 - 10 h, such as 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.

[0044] In some preferred embodiments, the vacuum degree of the vacuum sintering is 1.0×10 -3 ~4.0×10 -3 MPa, such as 1.0×10 -3 MPa, 2.0×10 -3 MPa, 3.0×10 -3 MPa, 4.0×10 -3 MPa, etc.

[0045] In some preferred embodiments, the heating rate of the vacuum sintering is not higher than 10 °C / min.

[0046] In some preferred embodiments, the cooling after the vacuum sintering is as follows: cooling at a cooling rate not higher than 5 °C / min until the temperature is below 1400 °C and then cooling with the furnace.

[0047] In some embodiments, during the vacuum sintering process, the first sintering material is put into a graphite crucible, and then the graphite crucible is placed in a sintering furnace for vacuum sintering. The sintering furnace for the vacuum sintering is a vacuum sintering furnace, and the heating methods can be graphite heating, molybdenum heating, induction heating, etc.

[0048] In some preferred embodiments, the granulation includes: mixing tantalum pentoxide powder with an appropriate amount of water, standing after mixing, and then screening to obtain a mixed material, and subjecting the mixed material to pressure granulation.

[0049] In some preferred embodiments, the mass ratio of the tantalum pentoxide powder to water is 6 - 9:4 - 1, such as 6:4, 6.5:3.5, 7:3, 7.5:2.5, 8:2, 8.5:1.5, 9:1, etc.

[0050] In some preferred embodiments, the mixing is carried out by a mixer; the mixing duration is 2 - 10 h; the standing duration is 20 - 30 h.

[0051] In some preferred embodiments, the pressure for the pressure granulation is 15 - 40 MPa, such as 15 MPa, 18 MPa, 20 MPa, 22 MPa, 25 MPa, 28 MPa, 30 MPa, 32 MPa, 35 MPa, 38 MPa, 40 MPa, etc.

[0052] In some preferred embodiments, the forming densities of the first press forming and the second press forming are independently 3.2 to 4.0 g / cm 3 , such as 3.2 g / cm 3 , 3.3 g / cm 3 , 3.4 g / cm 3 , 3.5 g / cm 3 , 3.6 g / cm 3 , 3.7 g / cm 3 , 3.8 g / cm 3 , 3.9 g / cm 3 , 4.0 g / cm 3 and so on. It has been found through research that too low a forming density will result in a low particle density after sintering, and too high a forming density will make it difficult to break the formed product, with a large workload and impurities easily introduced during breaking. 3.2 to 4.0 g / cm 3 is the forming density with the best effect.

[0053] In some preferred embodiments, the second sintered material is sieved and assembled into a particle aggregate, including: the second sintered material is sieved to obtain particles with a particle size of 0.5 to 3 mm, and then the obtained particles are assembled into a particle aggregate with a loose density of 4.0 to 4.3 g / cm 3 .

[0054] In some preferred embodiments, the purity requirement of the tantalum pentoxide powder is ≥99.95%.

[0055] In some preferred embodiments, the particle size D50 of the tantalum pentoxide powder is 0.3 to 2.5 μm, further preferably 0.3 to 2.2 μm, and even more preferably 0.3 to 2 μm, such as 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, etc.

[0056] To facilitate the understanding of the present invention, the present invention will be described more comprehensively and in detail below in conjunction with the accompanying drawings of the specification and preferred embodiments, but the protection scope of the present invention is not limited to the following specific embodiments.

[0057] Example 1 This example provides a high-density and high-transmission tantalum pentoxide optical coating material, which is black deoxidized tantalum pentoxide, and the atomic ratio of tantalum to oxygen in the tantalum pentoxide in the material is 2:4.95.

[0058] This embodiment also provides a preparation method of a high-density and high-transmission tantalum pentoxide optical coating material, which includes the following steps: Step S1, weigh 900 g of white tantalum pentoxide powder with a purity of 99.95% and a particle size D50 = 0.4 μm and 100 g of pure water, add them to a mixer and mix for 2 h. Immediately let the powder stand for 20 h to make the powder and water fully and evenly combine. Then, take out the powder after sieving and record it as mixture 1; Step S2, use a pressing granulator to press and granulate mixture 1 under a pressure of 25 Mpa to obtain granulated material 1; Step S3, crush granulated material 1 and then sieve it through a 80-mesh sieve to obtain granulated material 2; Step S4, press and form granulated material 2 according to a molding density of 4.0 g / cm 3 to obtain formed material 1; Step S5, crush the particles of formed material 1 and then sieve them. Collect the particles with a particle size of 1 - 5 mm. Grind the particles with a particle size less than 1 mm and then press and form them according to a molding density of 4.0 g / cm 3 to obtain formed material 2. The formed material is subjected to secondary crushing and sieving to obtain particles with a particle size of 1 - 5 mm. The particles with a particle size greater than 5 mm are crushed again and then sieved to obtain particles with a particle size of 1 - 5 mm; Step S6, mix the particles with a particle size of 1 - 5 mm obtained in step S5, place them in an alumina crucible, and then place the crucible in a sintering furnace for primary sintering (the sintering atmosphere is air). The primary sintering temperature is between 1400 °C and keep it warm for 6 h. Control the heating rate at 10 °C / min and the cooling rate at 5 °C / min. After cooling to 800 °C, cool it with the furnace to obtain sintered material 1; Step S7, transfer sintered material 1 to a graphite crucible, and then place the graphite crucible in a vacuum sintering furnace for secondary sintering. The secondary sintering temperature is 1650 °C and keep it warm for 2 h. The vacuum degree is 3.5×10 -3 MPa. Control the heating rate at 10 °C / min and the cooling rate at 5 °C / min. After cooling to 1400 °C, cool it with the furnace to obtain sintered material 2; Step S8, perform screening treatment on sintered material 2 to obtain particles with a particle size of 0.5 - 3 mm. Then, configure the obtained particles into an aggregate with a loose packing density between 4.3 g / cm 3 to obtain the black oxygen-deficient tantalum pentoxide optical coating material.

[0059] Example 2 The difference between this embodiment and Example 1 is only that in step S1, the particle size D50 of the tantalum pentoxide powder is 0.6 μm.

[0060] This embodiment provides a high-density and high-transmittance tantalum pentoxide optical coating material, which is black oxygen-deficient tantalum pentoxide, and the atomic ratio of tantalum to oxygen in the tantalum pentoxide in the material is 2:4.95.

[0061] This embodiment also provides a preparation method of the above-mentioned high-density and high-transmittance tantalum pentoxide optical coating material, which includes the following steps: Step S1, weigh 900 g of white tantalum pentoxide powder with a purity of 99.95% and a particle size D50 = 0.6 μm and 100 g of pure water, add them to a mixer and mix for 2 h. Then, let the powder stand for 20 h to make the powder and water fully and evenly combined. Then, take out the powder after sieving and record it as mixture 1; Step S2, use a compaction granulator to compact and granulate mixture 1 under a pressure of 25 Mpa to obtain granulated material 1; Step S3, crush granulated material 1 and then sieve it through a 80-mesh sieve to obtain granulated material 2; Step S4, compact granulated material 2 according to a molding density of 4.0 g / cm 3 to obtain molded material 1; Step S5, crush the particles of molded material 1 and then sieve them. Collect the particles with a particle size of 1 - 5 mm. Grind the particles with a particle size less than 1 mm and then compact them according to a molding density of 4.0 g / cm 3 to obtain molded material 2. The molded material is subjected to secondary crushing and sieving to obtain particles with a particle size of 1 - 5 mm. The particles with a particle size greater than 5 mm are crushed again and then sieved to obtain particles with a particle size of 1 - 5 mm; Step S6, place the particles with a particle size of 1 - 5 mm obtained in step S5 in an alumina crucible, and then place the crucible in a sintering furnace for primary sintering (the sintering atmosphere is air). The primary sintering temperature is between 1400 °C and keep it for 6 h. The vacuum degree is 3.5×10 -3 MPa, control the heating rate at 10 °C / min, and the cooling rate at 5 °C / min. After cooling to 800 °C, cool it with the furnace to obtain sintered material 1; Step S7, transfer sintered material 1 to a graphite crucible, and then place the graphite crucible in a vacuum sintering furnace for secondary sintering. The secondary sintering temperature is 1650 °C and keep it for 2 h. Control the heating rate at 10 °C / min, and the cooling rate at 5 °C / min. After cooling to 1400 °C, cool it with the furnace to obtain sintered material 2; Step S8, sieve sintered material 2 to obtain particles with a particle size of 0.5 - 3 mm, and then configure the obtained particles into an aggregate with a loose packing density between 4.3 g / cm 3 to obtain the black oxygen-deficient tantalum pentoxide optical coating material. The XRD analysis pattern of the obtained black oxygen-deficient tantalum pentoxide optical coating material is as Figure 1 shown, fromFigure 1 It can be seen that the main phase of the prepared coating material is high-temperature tetragonal α-Ta 2 O 5 .

[0062] Example 3 This example is basically the same as Example 1, except that the particle size of the tantalum pentoxide powder in step S1 is different.

[0063] Specifically: Step S1, weigh 900 g of white tantalum pentoxide powder with a purity of 99.95% and a particle size D50 = 2.5 μm and 100 g of pure water, add them to a mixer and mix for 2 h. Immediately let the powder stand for 20 h to make the powder and water fully and evenly combined. Then, sieve the powder and take it out, denoted as mixture 1.

[0064] Comparative Example 1 This comparative example is basically the same as Example 1, except that only the particle size of the tantalum pentoxide powder in step S1 is different.

[0065] Specifically: Step S1, weigh 900 g of white tantalum pentoxide powder with a purity of 99.95% and a particle size D50 = 3.7 μm and 100 g of pure water, add them to a mixer and mix for 2 h. Immediately let the powder stand for 20 h to make the powder and water fully and evenly combined. Then, sieve the powder and take it out, denoted as mixture 1.

[0066] Comparative Example 2 This comparative example is basically the same as Example 1, except that only the particle size of the tantalum pentoxide powder in step S1 is different.

[0067] Specifically: Step S1, weigh 900 g of white tantalum pentoxide powder with a purity of 99.95% and a particle size D50 = 5.0 μm and 100 g of pure water, add them to a mixer and mix for 2 h. Immediately let the powder stand for 20 h to make the powder and water fully and evenly combined. Then, sieve the powder and take it out, denoted as mixture 1.

[0068] Comparative Example 3 The difference between this comparative example and Comparative Example 2 is only that step S7 is different. Specifically, step S7 is as follows: Step S7, transfer the sintered material 1 to a graphite crucible, then place the graphite crucible in a vacuum sintering furnace for secondary sintering. The secondary sintering temperature is 1600 °C and it is held for 2 h. Control the heating rate at 10 °C / min and the cooling rate at 5 °C / min. After cooling to 1400 °C, cool with the furnace to obtain sintered material 2.

[0069] The prepared tantalum pentoxide coating material is deposited into a film layer by a conventional coating method. The phase purity analysis spectra of the tantalum pentoxide coating materials prepared in Example 1 and Comparative Examples 1-3 and the transmittance analysis spectra of the film layers deposited with the corresponding tantalum pentoxide coating materials are as Figure 2 shown. It can be seen from Figure 2 that as the α-Ta 2 O 5 phase purity of the prepared tantalum pentoxide coating material increases, the transmittance of the deposited film layer also increases. This indicates that there is a positive correlation between the α-Ta 2 O 5 phase purity of the tantalum pentoxide coating material and the transmittance. Therefore, the transmittance of the deposited film layer can be improved by increasing the α-Ta 2 O 5 phase purity of the tantalum pentoxide coating material.

[0070] Example 4 This example is basically the same as Example 1, except that the vacuum sintering temperature in step S7 is different.

[0071] Specifically: Step S7: Transfer the sintered material 1 to a graphite crucible, then place the graphite crucible in a vacuum sintering furnace for secondary sintering. The secondary sintering temperature is 1750 °C and it is held for 2 h, the vacuum degree is 3.5×10 -3 MPa, control the heating rate at 10 °C / min, and the cooling rate at 5 °C / min. After cooling to 1400 °C, cool with the furnace to obtain the sintered material 2.

[0072] Example 5 This example is basically the same as Example 1, except that the vacuum sintering temperature in step S7 is different.

[0073] Specifically: Step S7: Transfer the sintered material 1 to a graphite crucible, then place the graphite crucible in a vacuum sintering furnace for secondary sintering. The secondary sintering temperature is 1800 °C and it is held for 2 h, control the heating rate at 10 °C / min, and the cooling rate at 5 °C / min. After cooling to 1400 °C, cool with the furnace to obtain the sintered material 2.

[0074] Example 6 This example is basically the same as Example 5, except that the molding density in steps S4 and S5 is different.

[0075] Specifically: Step S4: Compress the granulated material 2 at a molding density of 4.3 g / cm 3 to obtain the molded material 1; Step S5: The formed material 1 is crushed into particles and then sieved, that is, the particles with a particle size of 1 - 5 mm are collected. The particles with a particle size less than 1 mm are ground and then pressed into a formed material 2 according to a forming density of 4.3 g / cm 3 The formed material is subjected to secondary crushing and sieving to obtain particles with a particle size of 1 - 5 mm. The particles with a particle size greater than 5 mm are crushed again and sieved to obtain particles with a particle size of 1 - 5 mm.

[0076] The SEM image of the obtained black oxygen - depleted tantalum pentoxide optical coating material is as Figure 3 shown. From Figure 3 it can be seen that the obtained tantalum pentoxide coating material has good compactness.

[0077] Example 7 The difference between this example and Example 6 is only that the sintering temperature in Step S6 is different. Specifically: Step S6: The formed material 2 is placed in an alumina crucible, and then the crucible is placed in a sintering furnace for primary sintering (the sintering atmosphere is air). The primary sintering temperature is between 1000°C and it is kept warm for 6 h. The vacuum degree is 3.5×10 -3 MPa. The heating rate is controlled at 10°C / min, and the cooling rate is 5°C / min until it reaches 800°C and then it is cooled with the furnace to obtain the sintered material 1.

[0078] Example 8 The difference between this example and Example 7 is only that the particle size of the tantalum pentoxide powder in Step S1 is different.

[0079] Specifically: Step S1: Weigh 900 g of white tantalum pentoxide powder with a purity of 99.95% and a particle size D50 = 1.5 μm and 100 g of pure water, add them to a mixer and mix for 2 h. Then immediately let the powder stand for 20 h to make the powder and water fully and evenly combined. Then the powder is sieved and taken out and recorded as the mixed material 1.

[0080] The phase purity and particle density of the tantalum pentoxide optical coating materials prepared in each example and comparative example are detected. The phase purity detection is obtained by XRD detection, and the particle density detection is realized by the wax - sealing method density test. The results are shown in Table 1, where the phase corresponding to XRD - PDF#21 - 1198 is high - temperature tetragonal α - Ta 2 O 5 .

[0081] It can be seen from Table 1 that by comparing the performance of the tantalum pentoxide coating materials obtained in Examples 1 - 3 and Comparative Examples 1 - 2, as the particle size D50 of the initial raw material tantalum pentoxide powder increases, the α - Ta 2 O 5The phase purity decreases, and the relative density of the particles also decreases. Although tantalum pentoxide powder with a particle size D50 = 2.5 μm can be used to prepare a coating material with a phase purity above 96%, the relative density of the particles (relative density refers to the ratio of the measured density to the theoretical density) is less than 80%. The phase purity of the coating material prepared from tantalum pentoxide powder with a particle size D50 = 3.7 μm is less than 95%. This indicates that the preparation method provided by the present invention can prepare α-Ta 2 O 5 tantalum pentoxide coating material with high phase purity and good coating performance.

[0082] Comparing the properties of the tantalum pentoxide coating materials obtained in Examples 5 - 6 with those in Comparative Example 1, and the properties of the tantalum pentoxide coating materials obtained in Comparative Example 7 and Example 8, it can be seen that the sintering mechanism has a relatively obvious influence on the density of the coating material.

[0083] Table 1 The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. Tantalum oxide optical coating material, characterized in that: The tantalum oxide optical coating material is black oxygen-depleted tantalum pentoxide, and the main phase is α-Ta2O5, wherein the phase purity of α-Ta2O5 is ≥96%.

2. The tantalum oxide optical coating material according to claim 1, characterized in that: The tantalum oxide optical coating material satisfies at least one of (1) to (3): (1) The atomic ratio of tantalum to oxygen in the tantalum oxide optical coating material is 2:(4.6-4.98); (2) The bulk density of the tantalum oxide optical coating material is 4.0-4.3 g / cm 3 ; (3) The relative density of the tantalum oxide optical coating material is greater than 80%.

3. A method for preparing a tantalum oxide optical coating material, characterized in that: include: Tantalum pentoxide powder with a particle size D50 of 0.3-2.8 μm is granulated, crushed and passed through an 80-mesh sieve to obtain a granulated material; The granulated material is subjected to a first compression molding to obtain a first molding material; The first molding material is crushed into particles and sieved to obtain particles with a particle size of 1 to 5 mm; The particles with a particle size of 1 to 5 mm are sintered once to obtain a first sintered material; The first sintered material is subjected to vacuum sintering to obtain a second sintered material; The second sintered material is screened and assembled into a particle aggregate to obtain a tantalum pentoxide optical coating material.

4. The method for preparing the tantalum oxide optical coating material according to claim 3, characterized in that: The first molding material is crushed into particles and sieved, and the particles with a particle size of less than 1 mm are ground and pressed for a second time to obtain the second molding material. The second molding material is crushed and sieved to obtain particles with a particle size of 1-5 mm, and the particles with a particle size greater than 5 mm are crushed and sieved again to obtain particles with a particle size of 1-5 mm.

5. The method for preparing the tantalum oxide optical coating material according to claim 3 or 4, characterized in that: The sintering temperature of the primary sintering is 1000-1500° C.; the heat preservation time of the primary sintering is 1-6 hours; The heating rate of the primary sintering is not higher than 10℃ / min; The temperature reduction after the primary sintering is: cooling to below 800° C. at a cooling rate not higher than 5° C. / min and then cooling along with the furnace.

6. The method for preparing the tantalum oxide optical coating material according to claim 3 or 4, characterized in that: The temperature of the vacuum sintering is 1500-1800° C., and the insulation time of the vacuum sintering is 1-10 hours; The vacuum degree of the vacuum sintering is 1.0×10 -3 ~4.0×10 -3 MPa; The heating rate of the vacuum sintering is not higher than 10°C / min; The cooling after vacuum sintering is as follows: cooling to below 1400° C. at a cooling rate not higher than 5° C. / min and then cooling along with the furnace.

7. The method for preparing the tantalum oxide optical coating material according to claim 3 or 4, characterized in that: The granulation comprises: mixing tantalum pentoxide powder with an appropriate amount of water, allowing the mixture to stand, sieving the mixture to obtain a mixture, and pressing the mixture to granulate the mixture; Preferably, the mass ratio of the tantalum pentoxide powder to water is 6-9:4-1; Preferably, the mixing is carried out by a mixer; the mixing time is 2 to 10 hours; the standing time is 20 to 30 hours; Preferably, the granulation pressure is 15-40 MPa.

8. The method for preparing the tantalum oxide optical coating material according to claim 3 or 4, characterized in that: The molding density of the first compression molding and the second compression molding is independently 3.2-4.0 g / cm 3 .

9. The method for preparing a tantalum oxide optical coating material according to claim 3 or 4, characterized in that: The second sintering material is screened and assembled into a particle assembly, which includes: the second sintering material is screened to obtain particles with a particle size of 0.5-3 mm, and then the obtained particles are assembled into a loose density of 4.0-4.3 g / cm 3 of particle aggregates.

10. The method for preparing the tantalum oxide optical coating material according to claim 3 or 4, characterized in that: The purity of the tantalum pentoxide powder is required to be ≥99.95%; the particle size D50 of the tantalum pentoxide powder is 0.3~2.5μm, preferably 0.3~2μm.